Progress in the study of the leprosy reactions - SHE Xinyan; LIN Xiuqiu; LI Yang; LIN Junjie; WANG Xiaohua; AO Xian (Pifu-xingbing zhenliaoxue zazhi, 2025)
In this article, we systematically reviews the epidemiological characteristics, pathogenesis and risk factors, clinical manifestations, diagnosis and treatment strategies, and predictive biomarkers of leprosy reactions (LR). The integration of epidemiological data indicates that approximately 50% of leprosy patients worldwide still develop LR after multi-drug therapy (MDT). TNFSF15-TNFSF8 locus polymorphisms (such as SNP rs6478108) and TLR9, IL-6 gene variants are significantly associated with the genetic susceptibility to leprosy reactions in type Ⅰ (T1R) and type Ⅱ (T2R), respectively. Studies on immune mechanisms have shown that T1R is driven by the inflammatory cascade mediated by Th1/Th17 cells, while T2R is characterized by immune complex deposition and neutrophil infiltration. Studies further suggest that neutrophil/lymphocyte ratio, expression levels of CD86/CD80/CD40 and anti-PGL-1 can be used as biomarkers for early prediction and diagnosis. Glucocorticoids and thalidomide are the first-line treatments for leprosy reactions, and other drugs (such as methotrexate and TNF-α inhibitor) can be used to improve the prognosis of refractory cases. This review establishes a theoretical framework for the diagnosis and treatment of leprosy reactions (LR) and highlights the need to identify novel biomarkers to predict LR occurrence. Such advances can reduce disability rates and improve patient quality of life, offering valuable guidance for leprosy prevention and control strategies in developing countries.